2018
DOI: 10.1177/0016986217752107
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Gifted and Talented Identification Practices

Abstract: Researchers consider the underrepresentation of Black, Hispanic, and Native American students is largely due to the use of traditional methods of identification (i.e., IQ and standardized achievement tests). To address this concern, researchers created novel non-traditional identification methods (e.g., non-verbal tests, student portfolios, affective checklists). This metaanalysis of 54 studies, consisting of 85 effect sizes representing 191,287,563 students, provides evidence that non-traditional identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
118
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 110 publications
3
118
0
4
Order By: Relevance
“…Naglieri and Ford's results showed that the disbursement of a standard score of 125 (95th percentile) was equally distributed among Whites (5.6%), Blacks (5.1%), and Hispanics (4.4%). The findings from the meta-analysis conducted by Hodges et al (2018), however, showed no statistical significance in terms of gifted identification rates for Black and Hispanic students when using verbal or nonverbal identification methods.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Naglieri and Ford's results showed that the disbursement of a standard score of 125 (95th percentile) was equally distributed among Whites (5.6%), Blacks (5.1%), and Hispanics (4.4%). The findings from the meta-analysis conducted by Hodges et al (2018), however, showed no statistical significance in terms of gifted identification rates for Black and Hispanic students when using verbal or nonverbal identification methods.…”
Section: Introductionmentioning
confidence: 81%
“…Students who are Black, Hispanic, and American Indian have, in fact, been annually underrepresented in gifted education programs by at least 40% (Ford et al, 2008). Results from a recent meta-analysis of gifted studies, from 2002 to 2015, showed that Black, Hispanic, and American Indian students were about one third as likely to be identified for gifted education as were their White and Asian counterparts (Hodges, Tay, Maeda, & Gentry, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations